(untitled) (World Bulletin of Social Sciences, 2024)
The article shows the need for the development of domestic ecological tourism and state support in Uzbekistan on the example of countries where this type of tourism is actively developing. In the next decade, ecotourism is recognized as the most rapidly developing and promising direction of tourism in Uzbekistan. It was concluded that Uzbekistan is one of the promising countries for the development of ecotourism due to its huge natural potential, unique natural objects included in the list of UNESCO ’s natural heritage.